Dengue hemorrhagic fever: Comparison of patients with primary and secondary infections - Muhammad Khurram; Wajeeha Qayyum; Syed Jawad ul Hassan; Shamaila Mumtaz; Hamama Tul Bushra; Muhammad Umar (Elsevier, 2014)
Summary: Background: Dengue hemorrhagic fever (DHF) is considered to be associated with secondary dengue infection. This study was conducted to note frequency of primary and secondary dengue infection in DHF patients. Additionally these patients were compared in terms of age, gender, laboratory parameter, diseases severity and outcome. Materials and methods: In this cross sectional observational study DHF patients fulfilling DHF criteria of Dengue Expert Advisory Group (DEAG) were included and divided into groups based on dengue specific IgG positivity and ratio of IgM to IgG. Group I, patients with secondary dengue infection were IgG positive or their ratio of IgM to IgG was <1.2. Group II, primary dengue infection patients were IgG negative or their ratio of IgM to IgG was >1.2. The two Groups were compared for statistically significant association in terms of age, gender, laboratory parameter (at admission hematocrit [HCT], platelet, white blood cell [WBC] counts, alanine aminotransferase [ALT] value), severity (DHF or dengue shock syndrome), and outcome (recovered or expired). Results: Two hundred thirty-four DHF patients were included. 66.2% was male and 33.8% female. Mean patient age was 28.8 ± 12.4 years. Based on dengue markers results, 61.5% patients were categorized to Group I, and 38.5% to Group II. Statistically significant association between the two Groups was noted in terms of at admission platelet count, and ALT value, P value <0.05. Conclusion: Primary dengue infection is frequently associated with DHF. Patients with DHF caused by secondary dengue infection have lower at admission platelet counts and higher ALT value. Keywords: Dengue, Dengue hemorrhagic fever, Primary and secondary dengue infection, Platelet count, Alanine aminotransferase